Ligand Photo-Isomerization Triggers Conformational Changes in iGluR2 Ligand Binding Domain - Wolter, Tino (Public Library of Science, 2014)
Neurological glutamate receptors bind a variety of artificial ligands, both agonistic and antagonistic, in addition to glutamate. Studying their small molecule binding properties increases our understanding of the central nervous system and a variety of associated pathologies. The large, oligomeric multidomain membrane protein contains a large and flexible ligand binding domains which undergoes large conformational changes upon binding different ligands. A recent application of glutamate receptors is their activation or inhibition via photo-switchable ligands, making them key systems in the emerging field of optochemical genetics. In this work, we present a theoretical study on the binding mode and complex stability of a novel photo-switchable ligand, ATA-3, which reversibly binds to glutamate receptors ligand binding domains (LBDs). We propose two possible binding modes for this ligand based on flexible ligand docking calculations and show one of them to be analogues to the binding mode of a similar ligand, 2-BnTetAMPA. In long MD simulations, it was observed that transitions between both binding poses involve breaking and reforming the T686-E402 protein hydrogen bond. Simulating the ligand photo-isomerization process shows that the two possible configurations of the ligand azo-group have markedly different complex stabilities and equilibrium binding modes. A strong but slow protein response is observed after ligand configuration changes. This provides a microscopic foundation for the observed difference in ligand activity upon light-switching.